PENGEMBANGAN APLIKASI E-COMMERCE PADA PRODUK HANDMADE ROTAN MENGGUNAKAN METODOLOGI INCREMENTAL STUDI KASUS: DONA ROTAN RUMBAI - chintia romauli rambe Rambe; Kartina Diah Kesuma Wardhani, S.T.,M.T. (ABEC Indonesia, 2021)
Dona Rattan shop is a business that makes various products from processed rattan into works of art. The traditional sales system is considered no longer adequate for handling work processes, especially the difficulties experienced by customers in knowing what products are offered at the Dona Rattan Store, and the difficulty of customers who are far from the store to be able to place an order, having to come directly. to the store because the range of promotions is still limited around the tassel. An alternative solution to these problems is the Development of E-commerce Applications Using the Website-based Incremental Methodology and the test results show that all the features or functionality of the existing system are running as expected. Based on the results of the tests carried out, the percentage value of 93.5% (with the category strongly agree) which indicates that the Development of E-commerce Applications Using the Incremental Methodology (Case Study: Toko Dona Rattan) has been running as desired and has been accepted by users. Keywords: Dona Rattan Shop, web, e-Commerce, Incremental Method.